The Influence of Archive Management on the Work Efficiency of Attendants - Wana Wana; Muh. Darwis; Jamaluddin Jamaluddin (ASHA Publishing, 2024)
Work efficiency is the most important factor to achieve organizational goals. Work efficiency will be created if employees can meet the demands of their work so that work results will be better. The purpose of this study is to determine the influence of archive management on the work efficiency of employees at the Soppeng Regency Population and Civil Registration Office. This research is classified as a descriptive research with a quantitative approach. The sample in this study amounted to 49 employees of the Soppeng Regency Population and Civil Registration Office with census techniques. In this study, data collection was used observations, questionnaires, interviews, and documentation. Meanwhile, the data analysis technique in this study uses descriptive analysis and inferential statistical analysis. The results of the study explain that the archive management variable is in the very good category, while the employee work efficiency variable is in the very good category. Based on the correlation test of the two variables, namely archive management, it is shown that the work efficiency of employees has a moderate relationship. Based on the T test, conclusions were obtained if there was a positive impact and archive management had a major impact on employee work efficiency